Enhancement of organic household waste anaerobic digestion performances in a thermophilic pilot digester. (January 2021) - Saber, Meryem; Khitous, Mohamed; Kadir, Lamia; Abada, Sabah; Tirichine, Nassima; Moussi, Karima; Saidi, Amina; Akbi, Amine; Aziza, Majda
Abstract: Performances of organic household waste anaerobic digestion was investigated in a new horizontal thermophilic pilot digester of 50 L total capacity. The operation was performed under favorable conditions without any chemical additives. The presence of predigested cattle manure in the digester provided an interesting buffer capacity that was able to balance the produced fatty acids during the digestion process. The biomethane production reached 0.44 m 3 CH4 /Kg VS while achieving a COD removal of 70%.The operating time and the anaerobic digestion steps were shortened under thermophilic wet digestion. Only 4 days were sufficient to reach the daily maximum methane production (0.084 m 3 CH4 /(kgVS.day)) and 10 days to reach 80% of the overall biomethane potential. The process efficiency in removing volatile solid was found to be more than 35% within 5 days. Therefore, wet anaerobic digestion under thermophilic temperature is suitable for industrial scale anaerobic digestion of biowaste regarding the high biomethane yield, the large COD and solid removing and the shortness of process operating time. Highlights: High process performances under controlled thermophilic pilot scale digester. Favorable conditions with large buffer capacity and thermophilic wet digestion. Enhanced biogas production and organic solid removing without chemical additives. Volatile fatty acid analysis in household waste anaerobic digestion. Reduced process time for biowaste industrial scale anaerobic digestion.